Decolonising pedagogy in post-apartheid South Africa: the expanded understanding of Vygotsky’s theory and new postulates - Muthivhi, A.E. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only Context and relevance. The paper examines contemporary post-apartheid pedagogy and its underlying epistemologies that position teachers and their students as passively conforming to prescribed knowledge and concepts disconnected from practical realities, goals, and students' personal pursuit of meanings. Objective and Hypothesis. Such an approach, premised on values of adaptation to the status quo of preexisting models and procedures, fails to promote knowledge premised on values of contribution to collective social practices and self-identity development. Theoretical basis. That is, pedagogy so conceptualised in the logic of colonial orthodoxies and solipsistic epistemologies, inevitably denies students and their teachers their inherent capacities for agency and meaningful engagement with reality. Results and discussion. Therefore, in instantiating decolonising approach to pedagogy, a young student the teacher had deemed to be experiencing learning difficulties, enacts her embodied knowledge [1]and is thereby posited as debunking the logic of colonial epistemologies that underpin contemporary post-apartheid pedagogy. Conclusions. The student is therefore presented as enacting her culturally situated community practices and knowledge traditions which she embodies, despite the continued exclusion of such knowledge practices within contemporary post-apartheid pedagogy. [1]Translator's notes: Embodied knowledge is a concept according to which knowledge is not only theories and mental ideas but also related to our personal experience, sensations, and how our body interacts with the surrounding world. This approach suggests that we learn through practical actions and personal experience, demonstrating how the body helps us understand and perceive reality. The concept of embodied knowledge challenges the outdated view that mind and body are separate entities and emphasizes that bodily perception is important for developing our knowledge and skills. Контекст и актуальность. В статье анализируется современная педагогика в постапартеидской Южной Африке и ее основные идеи, которые представляют учителей и учеников как пассивных участников, просто следящих за установленными знаниями и концепциями. Эти знания часто оторваны от реальных условий, целей обучения и личных поисков смыслов самих учеников. Цель и гипотеза. Такой подход, который основывается на необходимости приспосабливаться к существующим моделям и правилам, не способствует развитию знаний, связанных с участием в общественных практиках и формированием личной идентичности. Иными словами, педагогика, которая основана на колониальных взглядах и замкнутых в своих представлениях знаниях, лишает учеников и учителей их естественной способности быть активными участниками и по-настоящему взаимодействовать с окружающей реальностью. Результаты. Таким образом, при использовании деколонизирующего подхода к обучению, ученица, которую учитель считал испытывающей трудности в обучении, проявляет свои знания через действия и тело (телесные знания)[1]. Выводы. Это показывает, что ученица оспаривает идеи колониальных способов мышления, которые лежат в основе современной педагогики в постапартеидской Южной Африке. При этом она демонстрирует свои культурные практики и знания, связанные с ее сообществом, несмотря на то, что такие знания и практики часто игнорируются или исключаются в современной системе образования. [1] Прим. перев.: Телесные знания (embodied knowledge) понятие, согласно которому знания - это не только теории и умственные идеи, но и то, что связано с нашим личным опытом, ощущениями и тем, как наше тело взаимодействует с окружающим миром. Этот подход говорит о том, что мы учимся через практические действия и личный опыт, показывая, как тело помогает нам понимать и воспринимать окружающую реальность. Концепция телесных знаний оспаривает устаревшее представление о том, что разум и тело - это разные вещи, и подчеркивает, что восприятие телом важно для того, чтобы развивать наши знания и навыки.